Morphological study of some species of invertebrates in Al-Diwaniyah City, Iraq. - Al-Jasimee, Ahmed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The current study has investigated the morphological identification of some snails ofClass Gastropoda in AL-Diwaniyah City in Iraq. The findings show that there are threefamilies of studied samples, and they are Viviparidae, Thiaridae, and Melanopsidae of thespecies that are Melanoides tuberculata, Bellamya bengalensis and Melanopsis nodosa.More studies should be conducted in this regard, for the fact that normal fauna isimportant in terms of local fauna, and they should be kept under monitoring to avoidspecies extinction.